Y-intercept A: (0, -8.4)
X-intercept B: (8, 0)
Step-by-step explanation:
![\begin{gathered} Given: \\ (3)/(4)x\text{ -}(5)/(7)y\text{ = 6} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3wiu31tdwsnklbhmfzsp2xv4rxbvuerkr4.png)
x-intercept is the value of x when y = 0
To get the x-intercept of the equation, we will substitute y with 0:
![\begin{gathered} (3)/(4)x\text{ - }(5)/(7)\left(0\right)\text{ = 6} \\ (3)/(4)x\text{ - 0 = 6} \\ (3)/(4)x\text{ = 6} \\ multiply\text{ through by 4:} \\ 3x\text{ = 6\lparen4\rparen} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hwqal7ya8cb8m9dy7a0k6lj4rj30x1h461.png)
![\begin{gathered} 3x\text{ = 24} \\ divide\text{ both sides by 3:} \\ (3x)/(3)\text{ = }(24)/(3) \\ x\text{ = 8} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/80f8sdhlbrcupv775c3ah812vv85gtmjo9.png)
x-intercept = 8
In ordered pair: (8, 0)
y-intercept is the value of y when x = 0
To get the y-intercept of the equation, we will susbtitute x with 0:
![\begin{gathered} (3)/(4)\left(0\right)\text{ - }(5)/(7)y\text{ = 6} \\ 0\text{ - }(5)/(7)y\text{ = 6} \\ -(5)/(7)y\text{ = 6} \\ multiply\text{ through by 7:} \\ -5y\text{ = 6\lparen7\rparen} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/afjuvalvf8grb9e5z2byojrci93yie11h6.png)
![\begin{gathered} -5y\text{ = 42} \\ divide\text{ both sides by -5:} \\ y\text{ = 42/-5} \\ y\text{ = -8.4} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3qtdjdetterxs4m3h7ieiqimsuy44tkzw8.png)
y-intercept = -8.4
In ordered pair: (0, -8.4)
Y-intercept A: (0, -8.4)
X-intercept B: (8, 0)